The relationship between satellite derived and ground measurement sugar-cane water use: the case of Hippo Valley Estates in Zimbabwe. - Matsa, Mark; Muyemeki, Luckson (Clarion University of Pennsyslavia, 2016)
Effective irrigation water management can only be achieved when up to date real time information on the irrigated area, crops grown, and the levels of crop water use are available. However, the spatial scale of most irrigation schemes limit effective collection of this data, since most schemes are covering hundreds to thousands of square kilometers. The rendering of data collection is both tedious and expensive, and it limits ground based monitoring of crop performance and production estimation. Employment of remote sensing, which uses synoptic and repetitive view, may be desired to compliment ground based methods. The research seeks to determine the relationship between satellite derived sugarcane water use and ground measured sugarcane water use at the study site, Hippo Valley Estates in Zimbabwe. It explores the application of remote sensing in estimating sugar cane water use by comparing the SEBAL (Surface Energy Balance Algorithm for Land) model of estimating evapotranspiration and the ground method of measuring sugar cane water use at Hippo Valley Estates. It is hypothesized that there is no significant relationship between Landsat Thematic Mapper images of derived sugar cane water use and the ground measured sugar cane water use. The research reveals that there is a significant (p<0.05) positive relationship (r=0.808466) between ground measured sugar cane water use and the Landsat derived satellite sugar cane water use. The study also reveals that the ground based method of measuring sugar cane water use has a major limitation of assuming spatial homogeneity for the ground values measured in different sections of Hippo Valley Estates unlike the satellite derived method of estimating sugar cane water use which gives actual values of evapotranspiration on a pixel by pixel basis. It is recommended that both of these methods are used simultaneously (satellite method should be used to monitor sugar cane water use, and validation tests for the results should be used through the ground method of measuring sugar cane water use).